CYBER SECURITY - Kenzhebayeva, Z.E.; Isabayeva, G.Zh.; Zhunusova, Zh.K. (Academic Journal of Physical and Chemical Sciences, 2018)
Cybersecurity today is a serious aspect in the protection of not only personal information, but above all, the activities of banks, enterprises and individuals engaged in or holding funds in the cryptocurrency. The world community is concerned about the growing cyber threat, as information is a valuable asset of any organization, and therefore the creation of cyber security is necessary by creating groups of highly qualified specialists to strengthen national security from external and internal threats. Kazakhstan has also taken steps in the field of information security in the field of information, but the low level of competitiveness of the Republic of Kazakhstan in one of the most promising areas in the IT industry to develop solutions in the field of information security does not allow to counter these threats. Addressing the issue of national security in the field of cyber technologies, the authors see not only the adoption of the best practices of some countries, but also examine the issue of purchasing foreign software.